Effect of Dietary Estradiol-17ß on the Feminization of Silver Perch, Bidyanus bidyanus (Mitchell, 1838) - Sulaeman; Fotedar, Ravi (World Aquaculture Society, 2016)
The silver perch, Bidyanus bidyanus (Mitchell 1838), displays sexual dimorphism in size, with females reaching larger maximum size than males. In an attempt to produce all-female populations, larvae at 30 d posthatching were fed an estradiol-17ß (E2) diet at dosages of 0, 60, and 120 mg'kg for 30 d. Histological examination of gonads revealed that all E2-supplemented diets resulted in significantly higher (P<0.05) feminization rates (97.22 - 100%) than did the control (39.69%) but with no difference between the two E2 diets (P>0.05). Female and male gonads were observed in fish fed the 60 mg E2/kg diet. No significant differences were observed in the survival rate, weight gain, gonad weight and length, specific growth rate (SGR), or gonadosomatic indexes, except for gonad length and SGR at the end of the experiment. Aothough the ovary length of fish fed the 60 mg E2/kg diet was significantly shorter than that of the control groups, no abnormalities were detected. In contrast, fish fed 120 mg E2/kg grew faster than the other fish and showed sexual dimorphism. Our results suggest that supplementation of E2 at 60-120 mg/kg diet could be applied to establish all -female populations of silver perch.